ORGANOPROTECTIVE EFFECTS OF BENASEPRIL IN PATIENTS WITH ARTERIAL HYPERTENSION - V. S. Zadionchenko; T. V. Adasheva; A. M. Shamshinova; I. Y. Malishev; E. B. Manukhina; A. Y. Bogolyubskaya; K. M. Golovanov; M. A. Arakelyan; O. L. Silakova (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To evaluate antihypertensive efficiency of benasepril therapy (Lotensin, Novartis) and its effects on microcirculation, endothelium function, system of cytoprotection, ophthalmoscopic and functional characteristics of eye retina in patients with arterial hypertension (AH). Material and methods. 40 patients with AH of 1-3 degree (AH1, AH2, and AH3) were studied. After wash-out period all patients were prescribed benasepril 5-10 mg daily. If necessary, hydrochlorothiazide 12,5 mg daily was added. Treatment lasted during 6 months. Patients were examined at the beginning and at the end of the study. Ambulatory blood pressure (BP) monitoring was carried out. Microcirculation was assessed by method of laser Doppler flowmetry. Stable plasma metabolites of nitric oxide (NO) were determined by spectral photometry. Cytoprotection was assessed by content of heat shock proteins (HSP70) in leucocytes of peripheral blood. Ophthalmoscopy, color and contrast static campimetry with evaluation of sensory-motor reaction (SMR) time in different fields of vision were carried out. Results. Therapy with benasepril allowed to improve daily profile of BP and to reach its target level in all AH patients. Number of patients with spastic type of microcirculation decreased. Functional condition of endothelium improved which revealed in normalization of endothelial production of NO. Therapy with benasepril resulted in intracellular HSP70 level decrease which testified restriction of cellular destruction. The cytoprotective effect of benasepril was stronger in patient with severe AH. Therapy with benasepril resulted in SMR time decrease which signifies its positive influence on retinal blood flow. Evaluation of contrast and color sensitiveness of retina allowed to reveal and quantitatively assess earlier dysfunctions of retinal tissue perfusion, compared to ophthalmoscopy. Conclusion. Benasepril is an efficient antihypertensive drug which improves microcirculation, endothelium function and retinal perfusion, has cytoprotective effect. Color and contrast static campimetry is an adequate method for quantitative assessment of retinal perfusion and allows objectively to evaluate damage of eye as target organ of AH.